28.2k views
0 votes
Graph the system of equations below on a plece of paper. What is the

solution?
y = 2x-3
y = -x + 3

2 Answers

5 votes

Answer:

Via Comparison method

2x-3 = -x+3

->

3x=6

->

x=2

Replacing X with 2 in the equations to find your Y

2(2)-3 = 1

-2+3 = 1

So:

X: 2

Y: 1

Explanation:

User Doug Kent
by
5.3k points
3 votes
Via Comparison method

2x-3 = -x+3
->
3x=6
->
x=2

Replacing X with 2 in the equations to find your Y

2(2)-3 = 1

-2+3 = 1

So:

X: 2
Y: 1
User Zarat
by
6.4k points